The Philosophy of Pancasila as The Grand Theory of Legal Research Based on Bibliometric Analysis - Martin Roestamy; Abraham Yazdi Martin; Radif Khotamir Rusli (Indonesian Journal of Social Research (IJSR), 2022)
Grand Theory is a prominent theory in macro to explain social life, history, and human experience. The research purpose is to find a mapping analysis with the VOSviewer application to carry out a bibliometric analysis of research in law. Research data was obtained through Publish or Perish software. The information data collected is the search result for the terms "Pancasila" and "Grand Theory" within the scope of the Crossref platform. From the search results, it’s found 1074 articles published between 2018 and 2022. Based on the findings, In 2018, 257 publications were published, decreased to 167 articles in 2019, and increased again to 275 articles in 2020, until slightly reduced to 228 in 2021. In 2022 there were 146 research publications related to Pancasila research as a grand theory published in the Crossref search. The value of bibliometric analysis in providing analytical data about what happened is demonstrated in this work. This research is intended to assist and become a resource for researchers in identifying research themes, especially in law.